Humanization of Chinese religion - Kosec, Maja Maria (Asian studies, 2023)
This article aims to compare two interpretations of the emergence of new religious and moral concepts and beliefs in the period between the Shang (1600?1046 BC) and the Western Zhou (1046?771 BC) dynasties. It critically compares the theories of Xu Fugu-an (1903?1982) and Li Zehou (1930?2021) on the process of humanization of Chinese religion. By emphasizing religious concepts such as Heaven, the Mandate of Heaven, the Way of Heaven on the one hand, and moral concepts such as virtue, reverence, and rituality on the other, the author illuminates the differences in each author’s interpreta-tion of the era in which Chinese culture moved away from religion and into the realm of humanism and ethics. This article reveals the reasons for these differences, which stem from the profound divergences in the basic methods of Li and Xu. While Li’s elaboration is based on philosophical approaches, Xu Fuguan’s understanding is based on philological and cultural analyses of the Chinese history of ideas. The author argues that these mutual differences between their interpretations demonstrate the importance of understanding different methodological approaches, which in turn allows for a deeper multi-layered un-derstanding of the process of humanization of Chinese religion.
Keywords: Heaven; humanizacija religije; humanization of religion; Li Zehou; Nebo; obred; ritual; Xu Fuguan